Dietary strategies to maintain adequacy of circulating 25-Hydroxyvitamin D concentrations - Kiely, Mairead; Black, Lucinda J. (Scandinavian journal of clinical & laboratory investigation. Supplement, 2012)
Abstract The importance of vitamin D intake to nutritional status is a corollary of sunshine deficit. There is a dose-response of serum 25-hydroxyvitamin D (25(OH)D) concentrations to total vitamin D intake in persons who do not receive UVB exposure. This updated summary of vitamin D intakes and sources in adults and children focuses on data from North America and Europe. We explore the evidence that intakes of vitamin D are inadequate with reference to the Institute of Medicine (IOM) Dietary Reference Intakes. Due to mandatory fortification, usual vitamin D intakes are higher in the US and Canada than most of Europe, with the exception of the Nordic countries. Intakes of vitamin D in national surveys are typically below 5 μg/d in most European countries and vary according to country-specific fortification practices, sex and age. The main source of variation is the contribution from nutritional supplements. Usual vitamin D intake estimates need to capture data on the contributions from fortified and supplemental sources as well as the base diet. The current dietary supply of vitamin D makes it unfeasible for most adults to meet the IOM Estimated Average Requirement of 10 μg/d. While supplements are an effective method for individuals to increase their intake, food fortification represents the best opportunity to increase the vitamin D supply to the population. Well-designed sustainable fortification strategies, which use a range of foods to accommodate diversity, have potential to increase vitamin D intakes across the population distribution and minimize the prevalence of low 25(OH)D concentrations.